Ectopic pregnancy: reappraisal of risk factors and management strategies - Mohan, Swapna; Thomas, Mariam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The incidence of ectopic pregnancy is increasing. The objective of this study was to analyze the risk factors, clinical characteristics, and management strategies in patients with ectopic pregnancy at a tertiary care referral centre in South India. Methods: Retrospective observational study was done for a period of seven years from April 2006 to March 2014 where in case files of 87 cases of ectopic pregnancies were analyzed for clinical profile, sonological data, management strategies and outcome. Results: The incidence of ectopic pregnancy has increased from 8.3 in 2006 to 18.92/1000 live births in 2014. Risk factors associated were prior tubal ligation 21 (24.14%), history of pelvic inflammatory disease 11 (12.64%), prior ectopic 5 (5.75%), prior tubal surgery 4 (4.60%), infertility 13 (14.94%), prior pelvic surgery 22 (25.29%) and current use of Copper T - 3 (3.45%) cases. Common symptoms were lower abdominal pain in 80 (91.95%) and amenorrhea in 76 (87.35) cases. 9 cases presented in shock. Gray scale ultrasound showed complex adnexal mass in 42 (48.28%), tubal ring 19 (21.84%) and live fetus in 11 (12.64%). 72 cases were managed surgically, 11 medically and 4 by expectant management. Tubal rupture occurred in 30(41.67%). Among those managed surgically, laparotomy was done in 55 (76.39%), laparoscopy in 17 (23.61%) cases. Salpingectomy was done in 52 (72.22%), salpingostomy 9 (12.5%), salpingotomy 5 (6.94%), segmental resection 3 (4.17%), scar excision and repair 1 (1.39%), abdominal hysterectomy 1 (1.39%), and laparotomy for abdominal pregnancy in 1 (1.39%) case. There was no maternal death. Conclusions: The incidence of ectopic has been increasing. Prior sterilization particularly done along with caesarean is the most common risk factor in our region. Surgical management by laparotomy and salpingectomy continues to be the preferred mode of management of ectopic pregnancy in our institution since two third of patients are referred from periphery and present with considerable intraperitoneal hemorrhage.